Asymptotic behavior of solutions of a third order nonlinear differential equation - Graef, J.R.; Remili, M. (Нелінійні коливання, 2017)
The asymptotic properties of solutions of some third order differential equation are examined. Sufficient conditions for the square integrability and oscillation of solutions are established.